2017
DOI: 10.1007/s10800-017-1100-3
|View full text |Cite
|
Sign up to set email alerts
|

Current efficiency of individual electrodes in the sodium chlorate process: a pilot plant study

Abstract: Current efficiency in the sodium chlorate process is a key issue in the evaluation of the power consumption. A pilot cell unit for executing the sodium chlorate process was constructed to study the current efficiency of the anode and cathode separately. The effects of sodium dichromate and sodium sulphate concentrations and the electrolyte temperature on the anode and cathode current efficiencies were studied. Corrosion products formed on the mild steel cathodes after their removal from the cell were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…This is also supported by results obtained for polished titanium and steel substrates, where it was shown that μM levels of chromate efficiently suppress hypochlorite reduction . However, in the commercial chlorate process, concentrations between 2–8 gL −1[48–49] are required to obtain 90–95% cathodic current efficiency . In a recent pilot study, it was shown that the cathodic current efficiency increased with increasing chromate concentration up to 5 gL −1 and then levelled off .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also supported by results obtained for polished titanium and steel substrates, where it was shown that μM levels of chromate efficiently suppress hypochlorite reduction . However, in the commercial chlorate process, concentrations between 2–8 gL −1[48–49] are required to obtain 90–95% cathodic current efficiency . In a recent pilot study, it was shown that the cathodic current efficiency increased with increasing chromate concentration up to 5 gL −1 and then levelled off .…”
Section: Resultsmentioning
confidence: 99%
“…However, in the commercial chlorate process, concentrations between 2–8 gL −1[48–49] are required to obtain 90–95% cathodic current efficiency . In a recent pilot study, it was shown that the cathodic current efficiency increased with increasing chromate concentration up to 5 gL −1 and then levelled off . These concentrations are higher than required to form a monolayer on the electrode surfaces (see SI for a rough estimate), The excess of chromate in the electrolyte is needed to assure that the surface is completely covered with chromium oxide/hydroxide and for mild steel electrodes some of it is consumed by incorporation in the corrosion layer formed during shut downs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the industrial process much larger concentrations of 2 to 8 g dm -3 are needed [50]. In a pilot plant, the cathodic current efficiency scaled with chromate concentration up to 5 g dm -3 [51]. These concentrations are much higher than required for the formation of a few monolayers, even when taking into account that some chromate is incorporated into the Fe during shutdowns [8], [51].…”
Section: Cathode Selectivitymentioning
confidence: 99%
“…In a pilot plant, the cathodic current efficiency scaled with chromate concentration up to 5 g dm -3 [51]. These concentrations are much higher than required for the formation of a few monolayers, even when taking into account that some chromate is incorporated into the Fe during shutdowns [8], [51]. These discrepancies in concentration indicate that the film growth process is influenced by the process conditions, and possibly also that the film formation by itself is not sufficient to achieve state-of-the-art efficiency.…”
Section: Cathode Selectivitymentioning
confidence: 99%